Genome-wide association study in patients with posterior urethral valves - van der Zanden, Loes F. M.; Maj, Carlo; Borisov, Oleg; van Rooij, Iris A. L. M.; Quaedackers, Josine S. L. T.; Steffens, Martijn; Schierbaum, Luca; Schneider, Sophia; Waffenschmidt, Lea; Kiemeney, Lambertus A. L. M.; de Wall, Liesbeth L. L.; Heilmann, Stefanie; et al. (Frontiers in Pediatrics, 2022)
Congenital lower urinary tract obstructions (LUTO) are most often caused by posterior urethral valves (PUV), a male limited anatomical obstruction of the urethra affecting 1 in 4,000 male live births. Little is known about the genetic background of PUV. Here, we report the largest genome-wide association study (GWAS) for PUV in 4 cohorts of patients and controls. The final meta-analysis included 756 patients and 4,823 on ethnicity matched controls and comprised 5,754,208 variants that were genotyped or imputed and passed quality control in all 4 cohorts. No genome-wide significant locus was identified, but 33 variants showed suggestive significance (P<1×10-5). When considering only loci with multiple variants residing within <10kB of each other showing suggestive significance and with the same effect direction in all 4 cohorts, 3 loci comprising a total of 9 variants remained. These loci resided on chromosomes 13, 16, and 20. The present GWAS and meta-analysis is the largest genetic study on PUV performed to date. The fact that no genome-wide significant locus was identified, can be explained by lack of power or may indicate that common variants do not play a major role in the aetiology of PUV. Nevertheless, future studies are warranted to replicate and validate the 3 loci that yielded suggestive associations.